DOMINANT FACTORS INFLUENCING THE LEVEL OF COMPLIANCE WITH THE USE OF PPE (AMONG CONSTRUCTION WORKERS IN REHABILITATION AND MAINTENANCE OF COMMUNITY HEALTH CENTER IN TUBAN DISTRICT) - Danang Setiawan; Nugrahadi Dwi Pasca Budiono (Universitas Kusuma Husada Surakarta, 2025)
Compliance to always wear personal protective equipment is one of the important factors in reducing the number of work accidents. Factors that become the basis for compliance behavior in wearing personal protective equipment are very diverse, one of which is company regulations, supervision, worker knowledge, availability of personal protective equipment, rewards and punishments, and worker attitudes. Research at the Tuban Regency Health Center aims to analyze the dominant factors that influence the level of compliance with the use of PPE in rehabilitation and maintenance construction workers. Quantitative research using observational methods and cross-sectional design. The study population involved rehabilitation and maintenance construction workers of Puskesmas in Tuban Regency, with a sample of 53 workers selected using probability sampling technique with simple random sampling. The level of compliance with the use of PPE as the dependent variable while knowledge, attitude, peer encouragement, HSE inspection, reward, and punishment as independent variables. The instrument used a questionnaire. Data analysis using Multiple Logistic Regression statistical test with SPSS. The test results obtained ap value <0.05, with the attitude variable having the highest Exp(B) value (14.423) compared to other variables, meaning that there is an influence of knowledge, attitude, peer encouragement, reward and punishment on the level of compliance with the use of PPE, and attitude is the most dominant factor. The suggestion for improvement is for the workforce to be more open to the concept of safety culture in the workplace.